Ácido graxo poli-insaturado ômega-3 e sua associação com a massa muscular de indivíduos participantes do National Health and Nutrition Examination Survey - Branco, Flávia Moure Simões de (2022)
Background: Omega-3 (ω-3) fatty acids have anti-inflammatory effects and can indirectly increase muscle protein synthesis, making muscle more sensitive to amino acid uptake; however, the association between plasma ω-3 and muscle mass in younger individuals is not well known. Furthermore, the influence of protein intake on muscle protein synthesis stimulated by ω-3 has been discussed. Aim: To evaluate the association between plasma ω-3 fatty acids and appendicular muscle mass index (IMMA) in young and middle-aged individuals and according to sex; and to evaluate the association between plasma ω-3 fatty acids and IMMA according to daily protein intake (<0.8 g/kg/day or ≥0.8 g/kg/day). Methods: This is a cross-sectional study that evaluated 1,037 individuals aged 20 to 59 years from the National Health and Nutrition Examination Survey (NHANES) 2011-2012. The gas chromatography mass spectrometry method was used to evaluate the plasma ω-3 fatty acids. Lean mass was assessed by dual energy X-ray absorptiometry (DXA) and IMMA (kg/m2) was calculated as appendicular lean mass (kg) divided by height squared. Linear regression analyzes were performed to assess the association between IMMA and total plasma ω-3, docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA) and alpha-linolenic acid (ALA) for the total sample, according to age (20 to 44 years and 45 to 59 years) and sex and separately by protein intake (low protein intake: <0.8 g / kg; or adequate: ≥0.8 g / kg). Results: Total ω-3 plasma, DHA, EPA, and ALA were not associated with IMMA in the total sample according to sex and age after adjustments for confounding factors. However, total ω-3, plasma ALA and DHA were positively associated with IMMA in individuals with low protein intake, but no association was observed in individuals with adequate protein intake. Conclusion: In conclusion, plasma ω-3 fatty acids are not associated with IMMA in young and middle-aged individuals, regardless of sex. However, plasma ω-3 fatty acids have been associated with IMMA in individuals with low protein intake.